Westonci.ca is the premier destination for reliable answers to your questions, brought to you by a community of experts. Join our Q&A platform to connect with experts dedicated to providing accurate answers to your questions in various fields. Join our Q&A platform to connect with experts dedicated to providing accurate answers to your questions in various fields.
Sagot :
Sure! Let's derive the equation of the line that passes through the point (6, -3) and has a slope of [tex]\( \frac{1}{2} \)[/tex].
1. Identify the form of the equation:
The general form of a line's equation with slope [tex]\( m \)[/tex] and passing through point [tex]\((x_1, y_1) \)[/tex] is given by the point-slope form:
[tex]\[ y - y_1 = m(x - x_1) \][/tex]
Here, [tex]\( m = \frac{1}{2} \)[/tex], [tex]\( x_1 = 6 \)[/tex], and [tex]\( y_1 = -3 \)[/tex].
2. Substitute the values:
Plugging these values into the point-slope form, we get:
[tex]\[ y - (-3) = \frac{1}{2}(x - 6) \][/tex]
Simplifying this, we obtain:
[tex]\[ y + 3 = \frac{1}{2}(x - 6) \][/tex]
3. Convert to slope-intercept form:
To convert to the slope-intercept form [tex]\( y = mx + b \)[/tex]:
[tex]\[ y + 3 = \frac{1}{2}x - \frac{6}{2} \][/tex]
[tex]\[ y + 3 = \frac{1}{2}x - 3 \][/tex]
4. Solve for [tex]\( y \)[/tex]:
Isolating [tex]\( y \)[/tex] on one side of the equation:
[tex]\[ y = \frac{1}{2}x - 3 - 3 \][/tex]
[tex]\[ y = \frac{1}{2}x - 6 \][/tex]
Hence, the equation of the line that passes through the point (6, -3) and has a slope of [tex]\(\frac{1}{2}\)[/tex] is:
[tex]\[ y = \frac{1}{2}x - 6 \][/tex]
So, the correct option is [tex]\(y = \frac{1}{2}x - 6\)[/tex].
1. Identify the form of the equation:
The general form of a line's equation with slope [tex]\( m \)[/tex] and passing through point [tex]\((x_1, y_1) \)[/tex] is given by the point-slope form:
[tex]\[ y - y_1 = m(x - x_1) \][/tex]
Here, [tex]\( m = \frac{1}{2} \)[/tex], [tex]\( x_1 = 6 \)[/tex], and [tex]\( y_1 = -3 \)[/tex].
2. Substitute the values:
Plugging these values into the point-slope form, we get:
[tex]\[ y - (-3) = \frac{1}{2}(x - 6) \][/tex]
Simplifying this, we obtain:
[tex]\[ y + 3 = \frac{1}{2}(x - 6) \][/tex]
3. Convert to slope-intercept form:
To convert to the slope-intercept form [tex]\( y = mx + b \)[/tex]:
[tex]\[ y + 3 = \frac{1}{2}x - \frac{6}{2} \][/tex]
[tex]\[ y + 3 = \frac{1}{2}x - 3 \][/tex]
4. Solve for [tex]\( y \)[/tex]:
Isolating [tex]\( y \)[/tex] on one side of the equation:
[tex]\[ y = \frac{1}{2}x - 3 - 3 \][/tex]
[tex]\[ y = \frac{1}{2}x - 6 \][/tex]
Hence, the equation of the line that passes through the point (6, -3) and has a slope of [tex]\(\frac{1}{2}\)[/tex] is:
[tex]\[ y = \frac{1}{2}x - 6 \][/tex]
So, the correct option is [tex]\(y = \frac{1}{2}x - 6\)[/tex].
Thank you for trusting us with your questions. We're here to help you find accurate answers quickly and efficiently. Thanks for using our service. We're always here to provide accurate and up-to-date answers to all your queries. Get the answers you need at Westonci.ca. Stay informed with our latest expert advice.